1990
DOI: 10.1128/aac.34.9.1733
|View full text |Cite
|
Sign up to set email alerts
|

Comparative postantibacterial activities of pefloxacin, ciprofloxacin, and ofloxacin against intracellular multiplication of Legionella pneumophila serogroup 1

Abstract: The inhibitory and postantibacterial activities of pefloxacin, ciprofloxacin, and ofloxacin against virulent Legionella pneumophila serogroup 1 were evaluated in cell-free and cellular models. In the absence of macrophages (with the tissue culture medium alone), bacterial numbers remained unchanged at 24 h in the presence of 0.1 ,ug of pefioxacin, ciprofloxacin, or ofloxacin per ml and 1.0 ,ug of pefloxacin per ml, whereas they were reduced in the presence of 1.0 ,ug of ciprofloxacin or ofioxacin per ml. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The approximate ratios of the cellular-to-extracellular ratios to the MICs for L. pneumophila for each drug tested are 900, 300, 3,000, and 80 for gemifloxacin, levofloxacin, pneumophila but do not correlate with their intracellular activities completely. A prolonged postantibiotic effect in macrophages, as observed in this study for gemifloxacin, has been regularly observed for fluoroquinolone antimicrobial agents and azithromycin tested using these methods (9,10,17,29). Some bacterial strain differences were noted in these experiments, with gemifloxacin and azithromycin appearing more active against intracellular strain F889 in comparison with strain F2111.…”
Section: Discussionsupporting
confidence: 74%
“…The approximate ratios of the cellular-to-extracellular ratios to the MICs for L. pneumophila for each drug tested are 900, 300, 3,000, and 80 for gemifloxacin, levofloxacin, pneumophila but do not correlate with their intracellular activities completely. A prolonged postantibiotic effect in macrophages, as observed in this study for gemifloxacin, has been regularly observed for fluoroquinolone antimicrobial agents and azithromycin tested using these methods (9,10,17,29). Some bacterial strain differences were noted in these experiments, with gemifloxacin and azithromycin appearing more active against intracellular strain F889 in comparison with strain F2111.…”
Section: Discussionsupporting
confidence: 74%
“…Levofloxacin at 1 mg/L has been shown to have bactericidal activity against intracellular organisms grown in guinea pig alveolar macrophages by reducing the viable counts of two isolates by 2–3 log 10 CFU/mL, and was significantly more effective than erythromycin in the same model [9]. Furthermore, the fluoroquinolones have also been shown to have a significant postantibiotic effect against L. pneumophila [23,24]. Uncontrolled clinical trials have shown that the newer fluoroquinolones, including levofloxacin, were effective in treating both community‐acquired and nosocomial infections [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin and ofloxacin at similar concentrations had inhibitory effects, with evidence of regrowth of the organism at 72 h. Because of the frequent addition of rifampin to patients seriously ill with infections caused by L. pneumophila, our time-kill curve studies included fluoroquinolone or erythromycin combinations with The mortality rate among patients with L. pneumophila infections continues to be high, especially in bacteremic, immunocompromised, and intubated patients (8,16,23,29). It is known from previous in vitro studies with and without the inclusion of macrophages that the effect of erythromycin on L. pneumophila is an inhibitory one (2,18,21,24,25,31,38). In vivo comparative drug studies of the doses and lengths of therapy needed in patients with different primary diseases are lacking (8,16,23,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%